System korekcyjno-wyrównawczy a konstytucyjnie założona koncepcja samorządu terytorialnego - Bogucka-Felczak, Monika (Uniwersytet Wrocławski. Wydział Prawa, Administracji i Ekonomii, 2019)
The aim of this study is to indicate the threshold conditions for the functioning of the corrective and compensatory system in the income system of local government units resulting from the constitutional concept of local government. The solutions adopted in the field of horizontal compensation of income potential of local government units should be determined each time by the constitutional principles of shaping the local government financial system in the state, including the legal nature of individual sources of territorial communities and legal guarantees of obtaining them by these entities, which in turn derive from the systemic concept this self-government in the state. In countries where the financial independence of territorial self-government, even if statutorily limited, is subject to constitutional protection, it is the legislator's responsibility to seek such solutions to mitigate the horizontal imbalance of revenues of local governments that have the least intervention. Corrective and compensatory payments should therefore be applied only when other horizontal income redistribution instruments fail, and only intervene, rather than as a permanent element of the local government unit revenue system.
Keywords: corrective-equalization system; local self-government